Efektivitas Semarang Creative Hub Dalam Upaya Pengembangan Ekonomi Kreatif di Kota Semarang - Aditya Kusumawardana; Ida Hayu Dwimawanti; Tri Yuniningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The creative economy sector is becoming a trend among economic actors in Indonesia, which includes 17 business subsectors. However, the implementation of creative economy development through creative centers in Semarang City has not been able to develop several types of subsectors. This study aims to analyze the effectiveness of Semarang Creative Hub as an effort to develop the creative economy in Semarang City. The theory used by researchers is the theory of effectiveness according to Nakamura and Smallwood. This research uses descriptive research method with qualitative approach. The purpose of this research is to analyze the effectiveness of Semarang Creative Hub as an effort to develop the creative economy in Semarang City and its inhibiting factors. The results revealed that the presence of Semarang Creative Hub has not been effective in developing the creative economy in Semarang City. The inhibiting factors that influence such as Environmental Conditions, Coordination between agencies, resources, and the involvement of implementing agents. Researchers recommend developing infrastructure and pursuing promotional strategies to encourage, develop, and introduce the results of the creative economy in Semarang City.